Safety and efficacy of endoscopic ultrasound-guided gastroenterostomy using double balloon occlusion methods: a clinical retrospective study in 36 patients with malignant gastric outlet obstruction - Xu, Guifang; Shen, Yonghua; Lv, Ying; Zhou, Xiaoliang; Li, Wen; Wang, Yi; Hassan, Shahzeb; Wang, Lei; Zou, Xiaoping (Endoscopy International Open, 2020)
Background and study aims Gastric outlet obstruction (GOO) is common in the late stage of many malignant tumors of the digestive system. Endoscopic ultrasound (EUS)-guided gastroenterostomy (EUS-GE) is commonly used for palliative treatment of malignant GOO. The objective of this study was to investigate the safety, efficacy, and prognosis of EUS-GE in treatment of malignant GOO in Chinese patients.Patients and methods This was a retrospective, single-center study with 36 consecutive patients with malignant GOO who were treated with EUS-GE. The main outcome measures were technical success rate, clinical success rate, incidence of adverse events (AEs), and median survival time.Results A total of 36 patients with malignant GOO underwent double-balloon-assisted EUS-GE between March 2017 and June 2019 in our hospital. GOO occurred mainly in elderly men (mean age 69.0 years, M:F 0.89). The most common etiology of GOO was pancreatic cancer (41.7 %). The most common obstruction site was the second part of the duodenum (63.9 %). The technical success rate was 100 % (36/36). The clinical success rate was 94.4 % (34/36). Median time for the total procedure was 52 minutes (range 34 – 156 min). Median time for determination of puncture site was 20 minutes (range 15 – 28 min). Median time between puncture and successful delivery of the stent was 38 minutes (range 19 – 128 min). The GOOSS score was 0.2 before EUS-GE. The GOO Scoring System (GOOSS) score was 2.2 at 15 days after the EUS-GE (P = 0.001). The GOOSS score was still higher than 2 during a median follow-up period of 89 days. AEs were observed in nine patients (25.0 %) and 13 total AEs occurred. One patient died as a result of delayed stent migration and bleeding. Mean length of hospital stay was 5.8 ± 4.7 days. The median survival period was 103 days. The rate of GOO recurrence was 2.7 % (1/36).Conclusion EUS-GE was associated with increased safety and efficacy for treatment of malignant GOO in Chinese Mainland.